(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Agrobacterium rhizogenes-mediated genetic transformation for the establishment of root culture lines was developed successfully in the critically endangered medicinal plant Swertia chirayita (Roxb.) H. Karst. The key factor for the successfull development of hairy root culture lines was the use of whole micropropagated plants as excised explants of any type did not show any response following infection with A. rhizogenes strains. Maximum root induction frequency (25 ± 4.4%) with 2 - 9 roots per node/intermodal cut site was obtained following infection with A. rhizogenes strain LBA9402. Spontaneous regeneration of shoot buds was observed in six 9402-transformed root lines maintained in phytohormone free N/5 basal medium. The shoot buds developed for regenerating whole rooted Ri-transformed plants in phytohormone free basal medium. Integration of rolA, rolB, rolC and rolD genes of TL-DNA was confirmed in Ri-transformed root lines and plants by PCR analysis. Ten fast growing Ri-transformed root lines were screened for production of principal secoiridoids, characteristics of the parent plants. The swertiamerin content varied from 0.042 to 0.207% in the transformed root lines after 4 weeks of culture in N/5 basal medium. Ri-transformed plants showed enhanced accumulation of swertiamerin as compared to non-transformed plants of similar age. This is the first report of swertiamerin production in hairy root cultures and transformed plants of S. chirayita thereby providing new avenue for large-scale production of secondary metabolites of S. chirayita.